Relationship between lower limb vascular characteristics, peripheral arterial disease and gait in rheumatoid arthritis. (27th October 2019) - Tehan, Peta Ellen; Stewart, Sarah; Chuter, Vivienne Helaine; Carroll, Matthew; Rutherfurd, Katelyn Jane; Brenton‐Rule, Angela
Abstract: Objectives: Rheumatoid arthritis (RA) is associated with higher risk of atherosclerotic vascular disease, including peripheral arterial disease (PAD). The aim of this study was to measure lower limb vascular characteristics (indicative of PAD), using non‐invasive chairside testing methods, in people with RA compared to matched controls, and to determine the association between vascular characteristics and gait velocity as a measure of functional capacity in people with RA. Methods: This was a cross‐sectional pilot study which measured lower limb vascular characteristics (bilateral continuous wave Doppler, toe brachial index [TBI] and ankle brachial index [ABI]) and gait velocity (6‐m walk test) in people with RA and controls. Differences in vascular characteristics between groups were determined using linear regression models, and associations between vascular characteristics and gait were determined using logistic regression models. Results: Seventy‐two participants were included: 34 participants with RA mean disease duration 26.2 (SD 12.1) and 38 age‐ and sex‐matched controls. The control group contained 30 females (79%), and the RA group had 28 females (82%). There were no significant differences between the RA and control groups for lower limb vascular characteristics. People with RA walked significantly slower compared to controls (1.10 m/s vs 0.91 m/s, P  < .001). People with RA who had abnormal TBI, or abnormal qualitative Doppler walked significantly slower compared to those with normal TBI (0.86 m/s vs 0.95 m/s, P  = .043 and 0.81 m/s, vs 0.93 m/s, P  = .028). There was no significant association between ABI and gait velocity. Conclusion: This study did not identify different lower limb vascular characteristics in people with RA compared to matched controls. However, in people with RA, abnormal Doppler and TBI results are associated with slower walking velocity.